Implementasi Game Edukasi 3D dalam Pembelajaran Bahasa Jepang pada Mahasiswa Universitas Almuslim dengan Unity Engine Menggunakan Metode Multimedia Development Life Cycle (MDLC) - Sarah Nadia; Riyadhul Fajri; Sriwinar (Fakultas Ilmu Komputer Universitas Almuslim, 2026)
This study aims to develop a 3D educational game as an interactive learning medium for Japanese language learning at Universitas Almuslim using the Multimedia Development Life Cycle (MDLC) method and Unity Engine. The research employs six MDLC stages: concept, design, material collecting, assembly, testing, and distribution. The game, entitled